Znaczenie pracy zawodowej dla osób po 60. roku życia - Pikuła , Norbert G. (Studia Edukacyjne, 2020)
The paper presents the results of research related to the importance of occupational work for retired people. Secondary data analysis was used. The results of the study were presented in two perspectives: the importance of work during the working life and after retirement age and retirement.